Coexistence of enterotoxigenic Staphylococcus aureus and cytotoxic Clostridium difficile as predisposing factors for septic shock in patients with inflammatory bowel disease - Parhizkar, Baran; Alebouyeh, Masoud; Dezfulian, Anahita; Rad, Masoumeh Azimi; Bahreini, Bahram; Nazemalhosseini, Ehsan; Aslani, Mohammad Mehdi; Zali, Mohammad Reza (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Superimposed infections in patients with inflammatory bowel disease (IBD) have drawn considerable attention in the disease managements that can lead to increased rates of colectomy and mortality. We followed a case of an IBD patient with severe bloody diarrhea (more than 10 times a day) and diffuse ulceration in his colon that mimicked a flare-up of IBD. Stool examination showed enteric overgrown enterotoxigenic Staphylococcus aureus (sea+) together with a low count of cytotoxic Clostridium difficile (tcdB+) bacteria. Antibiotic therapy with oral vancomycin as the sole in vitro determined effective drug normalized the patient’s clinical features. The patient died of post-surgical septic shock after colectomy that had been conducted because of deterioration of his clinical state one week after the antibiotic therapy. Sudden release of overgrown intestinal S. aureus superantigens (sea and peptidoglycan) with regard to the cooperative effect of C. difficile infection was suspected as a predisposing factor for severe disease.